مفردة قراءة ابن كثير المكي - موصلي، أبي موسى جعفر ابن مكي; مشهداني، خالد أحمد (Dimashq : Dar Sa'd al-Din lil-Tiba'ah wa al-Nashr wa-al-Tawzi', 2007)
Koran; criticism, interpretations etc.
Keywords: Qur'an; criticism, interpretation, etc; Qur'an -- Readings -- Early works to 1800